Pregabalin therapy versus interventional blocks in neuropathic pain: A cohort study - Marín-Medina, Daniel S. (2023)
Objective: tcompare the decrease in pain in patients with pregabalin therapy versus interventional blocks. Materials and methods: retrospective cohort study that included patients older than 18 years diagnosed with neuropathic pain from a reference center in Pereira, Colombia, between the years 2010-2016. The outcome was assessed at three months in each cohort and was defined as the change in pain intensity according to the visual analog pain scale. The comparison between cohorts and the effectiveness of the intervention was evaluated through repeated measures analysis with the generalized estimating equation. Results: a total of 1451 patients with pain were selected, of these, only 94 met the inclusion criteria. Sixty-two (66%) patients received a pharmacological scheme with pregabalin, and 32 patients (34%) underwent blockages. The pain intensity prior to pregabalin treatment was 7.3 ± 1.8 and 8.9 ± 1.2 in the group with blocks, p = 0.005. The intensity of posterior pain in the group with pregabalin was 3.5 ± 2.4, with an average improvement of 53.9%, while in the group with blocks, it was 2.5 ± 2 with an average improvement of 70.7%. Interventional management reduces pain 2.09 times more compared to pregabalin therapy (p <0.001). Conclusions: the use of interventional blocks in the treatment of neuropathic pain should be considered in patients with moderate to severe neuropathic pain.